Geld als Fiktion? Warum Geld kein Kredit ist und das Publikum so schwer von seiner Stabilität zu überzeugen ist - Ganßmann, Heiner (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2015)
Starting from frequent characterizations of modern money as a fiction, the text discusses the theoretical background of the idea that money once was something „real“ whereas now it amounts to no more than a fiction. The distinction has its roots in the conviction that only commodity money was (or is) something „real“, whereas credit money is held to be fictitious money. However, both forms of money are social constructions, one operating with a „natural“ base in the form of precious metals, the other in the context of a politically managed credit system with the central bank as the lead institution. The problem with the latter is that it is not well understood, as the article demonstrates by going through Keynes understanding of money in his Treatise and some of the recent literature. Another recently popular theoretical remedy to enlighten the public about the money it uses has been to declare that all money is credit. However this is a simplification that threatens to undermine the project of improving the general understanding of money as a prerequisite for more democratic decision-making in the wake of the financial and the Euro crises. The fiction concerning money that remains is that there can be such a thing as a monetary invariant.